THE ROLE OF PHYSICAL EDUCATION IN THE ADOPTION OF AN ACTIVE LIFESTYLE BY STUDENTS AT THE END OF SECONDARY SCHOOL: A SURVEY IN NORTH-EAST OF ITALY (Fiep Bulletin - online, 2014)
The main aim of the search is to identify the role of physical education in the choice of the lifestyle in 1469 students (male and female, 17-22 years) (Nuviala, 2010). Some anthropometric characteristics (BMI ), amount of physical activity (IPAQ-A), self-efficacy perception (PSE ), scholastic grades in physical education (EV – Values among 0÷10), and the gender of the teachers are been detected, in order to characterize the population and verify their (potential) role in the choice of lifestyles. This presentation, based on the results of 1469 subjects, concerns the characteristics of the students (males versus females), their opinions on physical education and the role it played in the adoption of their lifestyle. The study of the correlations among the parameters assessed and the justifications given by the students are still in progress. Males (M) show higher values than females (F) (p
Keywords: physical education; active lifestyle